Evaluating the disability employment gap and Its determinants: findings from a population-based cohort study in spinal cord injury - Sarki, Mahesh; Schwegler, Urban; Austin-Cliff, George; Aparicio, Mayra Galvis; Reuse, Christine; Brinkhof, Martin W. G. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionThe disability employment gap (DEG) is instrumental in monitoring social progress and employment inequalities. This study evaluated the DEG and its determinants among people with spinal cord injury (SCI) in Switzerland.MethodsEmployment data from three consecutive population-based surveys were analyzed and compared with the general Swiss population, matched according to sex, age, year, and region of residence. Mixed-effects Poisson regression modelling was applied to evaluate the determinants of labor market participation (LMP) and derive marginal predictions for the DEG.ResultsDEGs decreased over calendar time, with individuals with complete tetraplegia exhibiting the most substantial reduction (2012: −37%, 2022: −25%); however, their probability of LMP in 2022 remained 25% lower than those with incomplete paraplegia. The DEG marginally increased among those with the fewest years of education (0–9) (2012: −48.1%, 2022: −49.2%). Regional disparities were also observed.ConclusionsOur findings indicate improved LMP opportunities in the Swiss SCI population, but also highlight the need to promote access to quality employment opportunities, vocational education, and training programs for severely injured individuals with low education. Additionally, efforts should be made to ensure equal LMP prospects across Switzerland.